Direct Evidence of π–π Interactions in Transparent Organic–Inorganic Polymer Hybrids of Polystyrene and Silica Gel - Takeru Iwamura; Saki Okuzumi; Kaoru Adachi; Masashi Takahashi; Masashi Shiotsuki (Advances in Polymer Technology)
Polystyrene and silica gel polymer hybrids derived from polystyrene and phenyltrimethoxysilane via π–π interactions were synthesized by a slight modification of the previous method. Spectroscopic evidence of the π–π interaction is provided. The obtained polymer hybrids were optically transparent, and no phase separation was observed by scanning electron microscopy measurements. In the FT-IR spectrum of the resulting polymer hybrids, the absorption peaks corresponding to C–H wagging vibration shifted to a lower wavenumber range as the content of silica in the hybrids increased. A UV–vis spectrum of the polystyrene and silica gel polymer hybrids showed a shoulder peak at around 260 nm that shifted toward longer wavenumbers side as the content of silica increased. These results clearly indicate that π–π interactions contribute to the formation of these transparent hybrids.